PENERAPAN LATIHAN MOTORIK HALUS UNTUK MENINGKATKAN KEMAMPUAN MENULIS HURUF SISWA TUNAGRAHITA KELAS DASAR III DI SLB. NEGERI 2 MAKASSAR - Rahman, Abdul (Lembaga Penelitian Mahasiswa Penalaran UNM, 2020)
The aims of this study were to find out the writing ability and writing activeness of Elementary Class III tunagrahita students at SLB Negeri 2 Makassar through the application of fine motor training. This study used a classroom action research. The research subjects were two students with tunagrahita in Elementary Class III SLB Negeri 2 Makassar with data collection through test, documentation, and observation. Data analysis was performed by using descriptive-qualitative and quantitative analysis technique. The results showed that the ability to write letters of the Elementary Class III tunagrahita students at SLB Negeri 2 Makassar with the application of the fine motor training had a significant increase qualitatively from cycle I to cycle II. The application of this fine motor training showed the better result from cycle I to cycle II. The increase of student activities included the overall activities given to the students.Â Keywords: Fine Motoric, Writing Letters, Tunagrahita